2020
DOI: 10.1111/aogs.13823
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on concurrent aneuploidy screening and preimplantation genetic testing for hereditary disorders: What is the prevalence of aneuploidy and is there a clinical effect from aneuploidy screening?

Abstract: Introduction:In assisted reproductive technology, aneuploidy is considered a primary cause of failed embryo implantation. This has led to the implementation of preimplantation genetic testing for aneuploidy in some clinics. The prevalence of aneuploidy and the use of aneuploidy screening during preimplantation genetic testing for inherited disorders has not previously been reviewed. Here, we systematically review the literature to investigate the prevalence of aneuploidy in blastocysts derived from patients ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…It is apparent that, so far, the Nordic countries hesitate to implement PGT‐A clinically. The systematic review by Toft et al 4 regarding aneuploidy screening in PGT‐M/SR could not demonstrate an improved outcome, but the experience is sparse.…”
Section: Pgtmentioning
confidence: 99%
“…It is apparent that, so far, the Nordic countries hesitate to implement PGT‐A clinically. The systematic review by Toft et al 4 regarding aneuploidy screening in PGT‐M/SR could not demonstrate an improved outcome, but the experience is sparse.…”
Section: Pgtmentioning
confidence: 99%
“…However, the effect on miscarriage rates is contentious; some recent studies, including multi-centre randomized controlled trials, show a reduced risk of miscarriage ( Verpoest et al, 2018 , Scriven, 2020 ), while others found that it did not affect miscarriage rates ( Munné et al, 2019 , Murphy et al, 2019 , Sato et al, 2019 ), or that miscarriages were rare even following the implantation of embryos classified as ‘abnormal’ ( Patrizio et al, 2019 ). The reduction of implantation cycles is likewise contested; a recent systematic review of 26 studies on PGT-A confirms that the add-on should, in theory, be able to enhance clinical outcomes on a per-transfer basis, but finds that the ‘current available literature is sparse or of insufficient quality’ and concludes that the routine use of PGT-A ‘with the aim of improving clinical outcomes is not supported by substantial evidence’ ( Toft et al, 2020 ). ASRM notes that PGT-A may moreover decrease the birth rate per cycle as a result of the embryo’s culturing conditions and cell biopsy, which could adversely affect the embryo, or due to the risk of unnecessarily discarding embryos that are classified as ‘abnormal’ ( Penzias et al, 2018 ).…”
Section: Predicting Fertility: the Intensification Of Ivfmentioning
confidence: 99%
“…The failure of embryo to implant can be a consequence of female, male, or embryo factors, or the specific type of IVF protocol (Bashiri et al, 2018). The primary cause of failed embryo implantation in ART is considered aneuploidy (Toft et al, 2020).…”
Section: Failed Embryo Implantationmentioning
confidence: 99%
“…A small number of the cases processed makes it difficult to predict the trend of high pregnancy rates in the long run, but we associate those with the exclusion of embryonic factors of reproductive failure in all transferred embryos (aneuploid embryo rate 37.5%). However, it is highlighted that randomized controlled trials are needed to conclude the clinical effect of PGT-A for PGT-M (Toft et al, 2020).…”
Section: Selecting the Best Technology For Multifactor Preimplantation Genetic Testingmentioning
confidence: 99%